A Narrative Review: Hubungan Antara Kualitas Diet dan Prestasi Akademik pada Anak Sekolah - Zahroul Nur Khasanah (Lembaga Pengembangan Kinerja Dosen, 2026)
Academic performance in children can be influenced by various factors, including lifestyle behaviors such as diet. The quality of healthy and sustainable diets plays a crucial role in brain development and cognitive function among schoolchildren. Therefore, improving dietary habits to achieve optimal diet quality may be associated with better academic outcomes. This study aims to examine the association between diet quality and academic performance in a population of children. The research design was undertaken across four electronic databases, such as Google Scholar, PubMed, Scopus, and ScienceDirect, for studies published between 2015-2025. The inclusion criteria were studies conducted among school-aged children (5–13 years) that assessed and reported: (i) a measure of diet quality, (ii) a measure of academic performance, and (iii) the association between diet quality and academic performance. Most of the studies reviewed were cross-sectional in design (n = 7). The majority of the findings reported a positive association between diet quality and academic performance, with higher diet quality generally linked to better academic outcomes. However, one study found that this correlation was stronger in boys than in girls. These findings highlight a consistent relationship between diet quality and academic performance in children. It is recommended that schools implement nutrition education and provide healthy food programs to support children's academic performance.